Two new species of the genus Zercon C. L. Koch from the Inner Aegean Region of Turkey (Acari: Mesostigmata: Zerconidae). Issue 2 (2nd April 2016) - Urhan, Raşit; Duran, Elif Hilal; Karaca, Mehmet
Abstract : Two new species of the mite genus Zercon C. L. Koch, 1836 have been found: Zercon ekizi sp. n. and Zercon emirdagicus sp. n. are described and illustrated from female specimens collected in Afyonkarahisar and Kütahya provinces, Turkey. The similarities and differences between the related species are discussed. http://www.zoobank.org/urn:lsid:zoobank.org:pub:7388D199-2D1D-49F7-9747-4F49E8810067